DESAIN WEBSITE INTERAKTIF SASTRA DAERAH "GO'ET" UNTUK ANAK SEKOLAH DASAR INPRES CUNCA LAWIR - faran, sefri; Swandi, Wayan; Sustiawati, Ni Luh (Segara Widya : Jurnal Penelitian Seni, 2025)
Go’et is a form of traditional oral literature that can be an effective medium for educating the Manggarai people, as it contains moral, social, and cultural values that are closely related to everyday life. Through go’et, the younger generation can learn about local wisdom, ethics, and respect for tradition. However, in this modern era, go’et is increasingly rarely mastered and understood by the younger generation due to the lack of direct cultural inheritance. Therefore, it is important to introduce and teach go’et from an early age, especially through formal education, so that this cultural heritage remains preserved and is able to shape the character and identity of the nation’s future generations. Addressing this issue, go’et has now been incorporated as a core topic in local curriculum subjects at the elementary school level. SD Inpres Cunca Lawir is one of the schools integrating go’et into local curriculum learning. However, in classroom implementation, discussions on go’et still face challenges, particularly regarding limited supporting facilities. Therefore, innovative learning media are needed to support the learning process so that go’et material can be presented more effectively and engagingly to students. The government’s recommendations regarding digital learning provide a solution for addressing the go’et topic digitally. The learning media were designed using the ADDIE approach and S.P. Gustami’s creation method, resulting in an interactive website for Manggarai go’et regional literature. An interactive website was chosen because it allows students to engage actively, and the website is equipped with features such as learning materials, a glossary of terms, and quizzes to encourage active student interaction.